ANALISIS USAHATANI DAN KEMAMPUAN MEMBAYAR KREDIT PADA PETANI KARET EKS UPP TCSDP TALUK KUANTAN SUB UNIT MUARA LEMBU - Valentia, Astri; Hadi, Syaiful; Rifai, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objectives of this research are to analysis of rubberÂ farming system and loan repayment ability of rubber plantation of the farmers ex UPP TCSDP in Sub Unit Muara Lembu, Kuantan Singingi Regency. Survey method was conducted in 3 villages, involved Muara Lembu, Koto baru and Logas rubber farmers. Rubber plantation farmers taken by purposive amount 30 farmers as respondents, distributed 10 farmers in each village.The research result showed, that the rubber production of ex TCSDP plantation was 2146 kg ojol/year. The household farmer income was Rp. 48.718.147/year in average and the expenditure of household farmer was Rp. 19.783.266/year in average. The rest of the farmers ' credit with interest until 2015 is Rp. 3.543.422. There were 28 samples that have the ability to pay > 1 which means being able to pay the credits, but the 21 samples has not paid off until today with the biggest reason is the loss of information where to pay the debt.Â Keyword : rubber farmers, credit, productivity, TCSDP